2012
DOI: 10.3390/ijms13032951
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Novel Di-, Tri-, and Tetranucleotide Microsatellite Primers Suitable for Genotyping Various Plant Pathogenic Fungi with Special Emphasis on Fusaria and Mycospherella graminicola

Abstract: The goals of this investigation were to identify and evaluate the use of polymorphic microsatellite marker (PMM) analysis for molecular typing of seventeen plant pathogenic fungi. Primers for di-, tri-, and tetranucleotide loci were designed directly from the recently published genomic sequence of Mycospherlla graminicola and Fusarium graminearum. A total of 20 new microsatellite primers as easy-to-score markers were developed. Microsatellite primer PCR (MP-PCR) yielded highly reproducible and complex genomic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 37 publications
1
12
1
Order By: Relevance
“…From the results of our study (Figure 1), sizes of PCR fragments amplified from primers (AG)7C and (TCC)5 were as expected ranging from 250-2000 bp and 300-2000 bp, respectively. Meanwhile for primer (TAGG)4, the fragments amplified ranged from 500-1500 bp in range, however, as reported by Bahkali et al (2012) the expected size ranged from 200-2000 bp. For primer (TTTC)4, there are negative results and no amplifications produced even though modifications were made on the annealing temperature and PCR reaction volume.…”
Section: Microsatellite Analysis and Genetic Diversitysupporting
confidence: 48%
See 3 more Smart Citations
“…From the results of our study (Figure 1), sizes of PCR fragments amplified from primers (AG)7C and (TCC)5 were as expected ranging from 250-2000 bp and 300-2000 bp, respectively. Meanwhile for primer (TAGG)4, the fragments amplified ranged from 500-1500 bp in range, however, as reported by Bahkali et al (2012) the expected size ranged from 200-2000 bp. For primer (TTTC)4, there are negative results and no amplifications produced even though modifications were made on the annealing temperature and PCR reaction volume.…”
Section: Microsatellite Analysis and Genetic Diversitysupporting
confidence: 48%
“…For primer (TTTC)4, there are negative results and no amplifications produced even though modifications were made on the annealing temperature and PCR reaction volume. It can be concluded that this primer is not suitable for analysis on F. verticillioides and F. proliferatum and from all the results, only partial agreement can be made with previous study by Bahkali et al (2012).…”
Section: Microsatellite Analysis and Genetic Diversitymentioning
confidence: 41%
See 2 more Smart Citations
“…This made it possible to search for all scaffolds in one go. Screening the genome for microsatellite motifs was based on published data about existing motifs that were detected in T. virens by ISSR and RAMS analysis [31,32]. Microsatellite loci sufficiently flanked by unique sequences were selected for primer design using the Primer3 software [33] with parameter settings that included the GC-clamp option and an allowance for primer annealing at approximately 60 °C.…”
Section: Screening Of Databases and Primer Designmentioning
confidence: 99%